Pentingnya komunikasi dalam mengatasi kendala untuk UMKM - Affandy, Faza Ainunnisa (Maliki Interdisciplinary Journal, 2023)
The development of the MSME sector in Malang City cannot be separated from the support of the government as a policy maker and banks as capital providers. From the banking sector, credit for the MSME sector continues to grow. Based on data from Bank Indonesia Malang, the credit value for the MSME sector in Malang City was IDR 3.14 trillion in 2016, an increase from IDR 2.94 trillion in the previous year. In this context, the role of Public Relations (PR) is Communities are emerging as an invaluable tool for MSMEs. Public Relations helps MSMEs to build better communication, a positive image, increase visibility, and build strong relationships with various customers and the community. Good communication is also important. Good communication can help MSMEs build good relationships with suppliers, business partners and customers. Good communication can also help resolve customer complaints and increase customer satisfaction. In carrying out its role, improving the business image of the Indoburger Shop is also supported by external parties, namely by building good relationships with media relations as a PR strategy.